Financial Literacy, Legal Certainty, and FoMO in Gen Z Cryptocurrency Investment: Evidence from Surakarta - Gandi Bahtiar Upangga; Haq Muhammad Hamka Habibie Habibie (Jurnal Ekonomi Islam, 2026)
This study examines how financial literacy, digital currency investment laws, and the Fear of Missing Out (FoMO) attitude shape cryptocurrency investment decisions among Generation Z in Surakarta. Using a quantitative design, the analysis used multiple linear regression in SPSS 26. Respondents were selected using non-probability purposive sampling; application of the Lemeshow formula yielded a minimum of 96 participants, rounded up to 100. Data were collected via an online Google Forms questionnaire using a five-point Likert scale. The estimation results show that all three predictors—financial literacy, digital currency investment regulations, and FoMO—are positively and significantly associated with cryptocurrency investment decisions, whether tested individually or collectively. Among the three, financial literacy has the greatest impact, investment regulations rank second, and FoMO contributes the least. The model explains 80.6% of the variation in investment decisions. By integrating cognitive, structural, and psychosocial dimensions into a single framework within the context of young investors in medium-sized cities, this study enriches the behavioral finance literature. The findings suggest that strengthening financial literacy alongside legal certainty is key to fostering more rational investment behavior among the younger generation.